Preliminary data revealing efficacy of Streptococcus salivarius K12 (SSK12) in Periodic Fever, Aphthous stomatitis, Pharyngitis, and cervical Adenitis (PFAPA) syndrome: A multicenter study from the AIDA Network PFAPA syndrome registry - La Torre, Francesco; Sota, Jurgen; Insalaco, Antonella; Conti, Giovanni; Del Giudice, Emanuela; Lubrano, Riccardo; Breda, Luciana; Maggio, Maria Cristina; Civino, Adele; Mastrorilli, Violetta; Loconte, Roberta; Natale, Marco Francesco; et al. (Frontiers in Medicine, 2023)
Objective To evaluate the potential role of Streptococcus salivarius K12 (SSK12) in controlling febrile flares in patients with Periodic Fever, Aphthous stomatitis, Pharyngitis, and cervical Adenitis (PFAPA) syndrome. Further aims were to assess the impact of SSK12 on (i) flare duration, (ii) variation in the degree of the highest body temperature during flares, (iii) steroid-sparing effect, and (iv) change of PFAPA accompanying symptoms before and after SSK12 introduction. Patients and methods The medical charts from 85 pediatric patients with PFAPA syndrome (49 males and 36 females) enrolled in the AIDA registry and treated with SSK12 for a median period of 6.00 ± 7.00 months in the period between September 2017 and May 2022 were examined. Children recruited had a median time of disease duration of 19.00 ± 28.00 months. Results The number of febrile flares significantly decreased comparing the 12 months before [median (IQR), 13.00 (6.00)] and after SSK12 initiation [median (IQR), 5.50 (8.00), p < 0.001]. The duration of fever was significantly reduced from 4.00 (2.00) days to 2.00 (2.00) days [p < 0.001]. Similarly, the highest temperature in°C was found significantly lower in the last follow-up assessment [median (IQR), 39.00 (1.00)] compared to the period prior to SSK12 start [median (IQR), 40.00 (1.00), p < 0.001]. Steroid load (mg/year) of betamethasone (or any equivalent steroid) significantly decreased between 12 months before treatment with SSK12 [median (IQR), 5.00 (8.00) mg/year] and the last follow-up visit [median (IQR), 2.00 (4.00) mg/year, p < 0.001]. The number of patients experiencing symptoms including pharyngitis/tonsillitis (p < 0.001), oral aphthae (p < 0.001) and cervical lymphadenopathy (p < 0.001) significantly decreased following SSK12. Conclusion SSK12 prophylaxis given for at least 6.00 months was found to reduce febrile flares of PFAPA syndrome: in particular, it halved the total number per year of fever flares, shortened the duration of the single febrile episode, lowered body temperature by 1°C in the febrile flare, provided a steroid-sparing effect, and significantly reduced the accompanying symptoms related to the syndrome.